Increasing social-ecological resilience within small-scale agriculture in conflict-affected Guatemala - Hellin, Jon; Ratner, Blake D.; Meinzen-Dick, Ruth S.; Lopez-Ridaura, Santiago (Resilience Alliance, Inc., 2018)
Climate change scenarios suggest largely detrimental impacts on agricultural production from a deterioration of renewable natural resources. Over the last 15 years, a new field of research has focused on the interactions between climate and conflict risk, particularly as it relates to competition over natural resources and livelihoods. Within this field, there has been less attention to the potential for resource competition to be managed in ways that yield greater cooperation, local adaptation capacity, social-ecological resilience, and conflict mitigation or prevention. The challenge of increasing social-ecological resilience in small-scale agriculture is particularly acute in the socioeconomically and agroecologically marginalized Western Highlands of Guatemala. Not only is climate change a threat to agriculture in this region, but adaptation strategies are challenged by the context of a society torn apart by decades of violent conflict. Indeed, the largely indigenous population in the Western Highlands has suffered widespread discrimination for centuries. The armed conflict has left a legacy of a deeply divided society, with communities often suspicious of outsider interventions and in many cases with neighbors pitted against each other. We use the example of the Buena Milpa agricultural development project to demonstrate how grassroots approaches to collective action, conflict prevention, and social-ecological resilience, linking local stakeholder dynamics to the broader institutional and governance context, can bear fruit amidst postconflict development challenges. Examples of microwatershed management and conservation of local maize varieties illustrate opportunities to foster community-level climate adaptation strategies within small-scale farming systems even in deeply divided societies.